Release of mitochondrial dsRNA into the cytosol is a key driver of the inflammatory phenotype of senescent cells - Vanessa López-Polo; Mate Maus; Emmanouil Zacharioudakis; Miguel Lafarga; Camille Stephan-Otto Attolini; Francisco D. M. Marques; Marta Kovatcheva; Evripidis Gavathiotis; Manuel Serrano (Nature Communications, 2024)
Abstract The escape of mitochondrial double-stranded dsRNA (mt-dsRNA) into the cytosol has been recently linked to a number of inflammatory diseases. Here, we report that the release of mt-dsRNA into the cytosol is a general feature of senescent cells and a critical driver of their inflammatory secretome, known as senescence-associated secretory phenotype (SASP). Inhibition of the mitochondrial RNA polymerase, the dsRNA sensors RIGI and MDA5, or the master inflammatory signaling protein MAVS, all result in reduced expression of the SASP, while broadly preserving other hallmarks of senescence. Moreover, senescent cells are hypersensitized to mt-dsRNA-driven inflammation due to their reduced levels of PNPT1 and ADAR1, two proteins critical for mitigating the accumulation of mt-dsRNA and the inflammatory potency of dsRNA, respectively. We find that mitofusin MFN1, but not MFN2, is important for the activation of the mt-dsRNA/MAVS/SASP axis and, accordingly, genetic or pharmacologic MFN1 inhibition attenuates the SASP. Finally, we report that senescent cells within fibrotic and aged tissues present dsRNA foci, and inhibition of mitochondrial RNA polymerase reduces systemic inflammation associated to senescence. In conclusion, we uncover the mt-dsRNA/MAVS/MFN1 axis as a key driver of the SASP and we identify novel therapeutic strategies for senescence-associated diseases.